2010
DOI: 10.1016/j.febslet.2010.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism and physiological role of pexophagy

Abstract: a b s t r a c tPexophagy is a selective autophagy process wherein damaged and/or superfluous peroxisomes undergo vacuolar degradation. In methylotropic yeasts, where pexophagy has been studied most extensively, this process occurs by either micro-or macropexophagy: processes analogous to microand macroautophagy. Recent studies have identified specific factors and illustrated mechanisms involved in pexophagy. Although mechanistically pexophagy relies heavily on the core autophagic machinery, the latest findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 73 publications
3
111
0
Order By: Relevance
“…Thus, it appeared that the expression level of PLA/AT-3, increasing PLA 1 /A 2 activity 10-fold over the control cells, is sufficient to see the loss of peroxisomes. It has been reported that the quality and quantity of peroxisomes are maintained by peroxisome-specific autophagy, pexophagy (11,13). However, during the DOX-dependent reduction of peroxisomes, the activation of LC3, a marker of autophagy, was not observed.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Thus, it appeared that the expression level of PLA/AT-3, increasing PLA 1 /A 2 activity 10-fold over the control cells, is sufficient to see the loss of peroxisomes. It has been reported that the quality and quantity of peroxisomes are maintained by peroxisome-specific autophagy, pexophagy (11,13). However, during the DOX-dependent reduction of peroxisomes, the activation of LC3, a marker of autophagy, was not observed.…”
Section: Discussionmentioning
confidence: 79%
“…However, we could not rule out the possibility that the expression levels of these proteins were not high enough to overcome the effect of PLA/AT-3 on peroxisomal structure. Our finding might result from the enhanced clearance of peroxisomes by the selective autophagy "pexophagy" (11,13,35). We therefore examined whether PLA/AT-3 stimulates the conversion of LC3-I protein to its phosphatidylethanolamineconjugated form, LC3-II, which is known to occur during autophagosome formation (36).…”
Section: Expression Of Pla/at-3 Rapidly Causesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the ER and the process of autophagy would certainly have a tight physiological relationship. Organelles are also selectively delivered to lysosomes by macroautophagy, known as ERphagy (reticulophagy), mitophagy, or pexophagy (Kim et al 2007;Yorimitsu and Klionsky 2007a;Ding and Yin 2008;Todde et al 2009;Manjithaya et al 2010).…”
Section: Other Degradation Pathwaysmentioning
confidence: 99%